Estágio Profissional: O Caminho até à Docência - Fábio José Sousa Silva (2020)
As part of the curriculum plan for the 2nd year of the Master's in Physical Education Teaching in Elementary and Secondary Schools, the EP is a moment that allows EE to discover and develop themselves as teachers, emerge into the school community and demonstrate their skills and knowledge. With the help of the PO and the PC it is possible to take risks, to be more daring in the strategies and methods to be used, because of their supervision and guidance, the risks are controlled, which offers more security to the EE in its practice. This document aims to present and make known, in a broad way, my participation and intervention throughout the process of professional growth, but not only that of PE. In this way diverse themes are treated which allow me to trace the path I have travelled until I arrive at EP, during and after it. The EP went better than I expected, my relationship with the class was great, the relationship between the students was one of friendship and mutual help. Therefore, I can focus largely on the preparation and execution of the teaching/learning process. As a teacher, I have a preference for constructivist approaches that promote a global and integral development of students. All my actions will be guided by the intention of giving students an important role in their learning, through the understanding of the contents, the power of decision and the attribution of responsibility. The integration in the school community is an important part of the EP process, the example and sympathy of all the actors of the community, employees, teachers, direction, etc., served as an example and facilitated my integration and participation in the activities organized by the school, the physical education group and the NE.